Teaching English Medical Writing in a Blended Setting - Arani, Jafar Asgari (International Journal of Emerging Technologies in Learning (iJET), 2012)
Medical writing activities which may have a context and seem to be engaging may be perceived as demotivating by the students of medicine. This opinion was confirmed by the learners' responses to the open-ended question given to them prior to this study. In their responses students evaluated the writing section of English course negatively. The negative views about the writing course posed a problem to the class teacher. The computer technology and the Internet can easily be integrated into language classroom if activities are designed carefully, and carried out systematically. These attempts brought about a new understanding to teaching and learning: blended learning (BL). The purpose of this research was to investigate students of medicine attitude to blended writing classes. It was conducted with second year learners in the Faculty of Medicine at Kashan University of Medical Sciences. The first reflection aimed at finding out medical students' attitude toward blended writing lessons. Although learners' attitude to writing lessons was negative in the first reflections, they changed into positive in the latter ones. The findings indicated that blended writing class had changed students' perception of writing lessons positively. Therefore, this kind of classes may help students develop a positive attitude towards writing by providing meaningful writing opportunities. Like the student portfolio before it, the weblog faces challenges with practicality and security, but ultimately provides an alternative way to teach and assess authentic writing and reading skills. Blog Assisted Language Learning not only provides teachers with an exciting new way to approach communicative language learning, it also gives the students a new reason to enjoy writing! The paper concludes that Internet tools have the potential to be a transformational technology for teaching and learning writing, and teachers ought to give strong consideration to the setting up their facilities within their learning management system.